Immobilization of Saccharomyces cerevisiae in Jackfruit (Artocarpus heterophyllus) Seed Fiber for Bioethanol Production - Zuhriyan Ash Shiddieqy Bahlawan; Megawati Megawati; Astrilia Damayanti; Radenrara Dewi Artanti Putri; Ayu Nur Permadhini; Khoridatus Sulwa; Fahreza Pracenda Felicitia; Anggun Septiamurti (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Bioethanol is alternative renewable energy typically obtained from glucose through a fermentation process using Saccharomyces cerevisiae. In the bioethanol fermentation process using yeast, there are several inhibiting factors, such as a high concentration of substrate, ethanol as the product, and nutrients. The present study aimed to investigate the effect of fermentation time (12- 72 hours), immobilized carrier size (sizes of 0.5 cm3 , 1 cm3 , and 1.5 cm3 ), and medium pH (3.0, 4.0, and 5.0) on the ethanol fermentation process using immobilized yeast in jackfruit (Artocarpus heterophyllus) seeds and subsequently to compare its performance with a free cell system. The highest ethanol concentration (89.15 g/L) with a yield of 96.92% was obtained by immobilizing yeast in jackfruit seed at a fermentation time of 72 hours, carrier size of 0.5 cm3 , and medium pH of 5.0. When compared to the free cell system fermentation under identical operating conditions, immobilized yeast in jackfruit seed obtained 1.41 times higher ethanol concentration. Jackfruit seed also led to a higher ethanol concentration compared to other S. cerevisiae carriers. Altogether, our findings imply that jackfruit seed has great potential as a carrier of S. cerevisiae in the process of fermenting glucose into ethanol